Omnidirectional high reflector for Infrared wavelength - Thapa K.B.; Singh S.K.; Ojha S.P. (My University, 2025)
We have purposed the design of omnidirectional high reflectors with wide bandwidth (nearly 6300A 0) for the infrared wavelength. Using translational matrix method for numerical calculation, it is found that a complete photonic band gap high reflector covering the wavelength region 11500A 0 to 17800A 0 is obtained for the quarter wave stack air / (n L n H) 7 / air by using the tellurium (n=4.60) and TiO 2 (n=2.35) as material of high reflective index and SiO 2(n=1.45) low refractive index. Due to high refractive index of contrast of the structure i.e. SiO 2/tellurium, a large complete photonic band gap, omnidirectional high reflector, has been observed for the infrared wavelengths. This type of omnidirectional high reflector can be used in telecommunication. Besides this, we have studied the effective refractive indices (phase and group) of the proposed structures. It is observed that the effective refractive indices (phase and group) of the high omnidirectional reflector band are largely changed near the band edges due to the high refractive index of contrast, and the reflections from the internal interfaces of the structure. © Springer Science+Business Media, LLC 2006.